Suḵẖanistān : yaʻnī, majmūʻah-yi g̲ẖazaliyāt, Āl Inḍīyā mushāʻirah, Gorakhpūr, maʻ savāniḥ va taṣāvīr-i suḵẖanvarān - Miṣr, Rām Gopāl (SAMP early 20th-century Indian books project ;)
Collection of Urdu ghazals recited at a poets gathering, Gorakhpur.